Papillary carcinoma arising from thyroglossal duct cyst with thyroid and lateral neck metastasis - Yang, Song-I (Elsevier, 2013)
INTRODUCTION: Thyroglossal duct carcinomas (TGDC) are rare, with approximately 274 reported cases since the first report in 1915. The prevalence of carcinomas in surgically removed thyroglossal duct cyst (TGD) is less than 1%. The usual recommended treatment for this condition is the Sistrunk operation, but controversies remain regarding the need for total or partial thyroidectomy. PRESENTATION OF CASE: A 28-year-old woman was admitted to our hospital with the symptoms of painless midline neck swelling and growing mass. A preoperative computed tomography (CT) showed a 4 cm sized heterogeneous mass at the infrahyoid anterior neck. Ultrasonography of the neck additionally showed suspicious metastatic lymph node at right level VI, both level VI. The patient underwent a Sistrunk operation. The frozen section revealed papillary carcinoma arising from TGDC and also revealed metastatic papillary carcinoma in the right thyroid, at right level III and level VI. Total thyroidectomy, right modified radical neck dissection and central neck dissection were performed. The thyroid gland and TGD were confirmed papillary carcinoma. The dissected neck lymph nodes revealed metastatic papillary carcinoma. DISCUSSION: The usual recommended treatment for TGD is the Sistrunk procedure. There is controversy regarding whether total or partial thyroidectomy should be performed. CONCLUSION: Physicians should be aware of extended operation, including thyroidectomy and/or neck node dissection for TGDC with metastatic lesion of thyroid and neck node.